2022
DOI: 10.3389/feduc.2022.886726
|View full text |Cite
|
Sign up to set email alerts
|

Juxtaposing generic skills development in collaborative knowledge work competences and related pedagogical practices in higher education

Abstract: This study employs the term knowledge work competence to address generic aspects of higher education graduates’ expected learning outcomes. Twenty-eight higher education courses were investigated: 1069 students responded to the Collaborative Knowledge Practices (CKP) questionnaire to rate their self-evaluated competence development. From the same courses, 56 teachers provided descriptions of the course pedagogical practices. First, students’ self-reported generic collaboration competence gains were analyzed st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Parsons et al [27] used a similar analysis in their study about assignments at the elementary school level and Schoenfeld [62] used the same kind of coding schema. The qualitative levels were quantified from one to four and the frequencies of the codes were compared [64], following the example of Muukkonen et al [7]. Level four represented the most intensive or expertlike pedagogical practices of the investigated characteristics, level one did not include the practices.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Parsons et al [27] used a similar analysis in their study about assignments at the elementary school level and Schoenfeld [62] used the same kind of coding schema. The qualitative levels were quantified from one to four and the frequencies of the codes were compared [64], following the example of Muukkonen et al [7]. Level four represented the most intensive or expertlike pedagogical practices of the investigated characteristics, level one did not include the practices.…”
Section: Discussionmentioning
confidence: 99%
“…The epistemic challenge of a learning assignment offers opportunities to learn real knowledge and work practices (7). It relates both to the authenticity of practices compared to real-life challenges (discussed in the previous paragraphs), and to the complexity of the problem space.…”
Section: Characteristics Of Assignments Promoting Collaborative Worki...mentioning
confidence: 99%
See 1 more Smart Citation
“…Individuals should approach Internet-based information critically and constantly justify it for their problem-solving (Van Laar et al, 2017). Therefore, in their future professional lives, higher education students might need general and transferable skills, such as problem-solving, creative thinking and collaboration, which are defined as 21st-century skills (Muukkonen et al, 2022;Van Laar et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…There have also been a few studies which investigated the interplay between courses and soft skills. The work by Muukkonen et al (2022) studied the students' self-perceptions towards competence gains in 28 courses from two large Finnish universities. The study showed the effects of courses on skill growth to be statistically significant between courses.…”
Section: Introductionmentioning
confidence: 99%